Analisis Faktor Penentu Kebijakan Luar Negeri Rusia dalam Konflik Nagorno-Karabakh tahun 2012 – 2016 - Boy, Charel Pasifichus; Fasisaka, Idin; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   Russia's involvement in the Nagorno-Karabakh conflict has its own implications especially with its capacity as a mediator of conflict. Mediation efforts continue to be carried out by Russia both independently and collectively within the OSCE Minsk Group framework. On the contrary, Russia's role as a mediator failed to bring a peace agreement and the Nagorno-Karabakh conflict escalated. This situation raises the assumption that Russia acts as a mediator solely not to achieve conflict resolution but to fulfill its interests in the region. Based on the above idea, the emergence of this research is to analyze Russia's foreign policy determinants as mediator in the Nagorno-Karabakh conflict, especially in the period 2012 - 2016. This research is a qualitative-descriptive study using the concept of mediators, national interest and determinants of foreign policy as instruments of analysis.   Keywords : Russia, Nagorno-Karabakh Conflict, National Interest, Mediator